Biomodulatory Treatment Regimen, MEPED, Rescues Relapsed and Refractory Classic Hodgkin’s Disease - Lüke, Florian; Harrer, Dennis C.; Menhart, Karin; Wolff, Daniel; Holler, Ernst; Hellwig, Dirk; Herr, Wolfgang; Grube, Matthias; Vogelhuber, Martin; Reichle, Albrecht; Heudobler, Daniel (Frontiers in Pharmacology, 2021)
Introduction: Current combined intensive chemotherapy and radiation regimens yield excellent survival rates in advanced classic Hodgkin’s lymphoma (cHL). However, acute toxicity in elderly, comorbid patients can be challenging and long-term survival in refractory patients remains poor. Patients and Methods: Three patients (age 21, 55 and 71 years) with refractory or relapsed cHL, stage IIIA (n=1) or IVB (n=2) received MEPED (treosulfan 250 mg p.o. daily, everolimus 15 mg p.o. daily to achieve serum trough levels of 15 ng/ml, pioglitazone 45 mg p.o. daily, etoricoxib 60 mg p.o. daily and dexamethasone 0.5 mg p.o. daily). Patients had either received every approved systemic treatment or were ineligible for standard treatment, including immune checkpoint inhibitor (ICPi) therapy due to prior demyelinating autoimmune polyneuropathy, myasthenia gravis and previous allogeneic hematopoietic-stem-cell transplant (alloHSCT), respectively. Medication was administered continuously from day 1. One patient with relapse after alloHSCT received trofosfamide 50 mg daily instead of treosulfan to avoid risk of increased myelotoxicity. The patients were treated in individual healing attempts outside a clinical trial after institutional review board approval. 18F‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography combined with computed tomography scan (FDG-PET/CT) was performed to monitor treatment and follow-up. Results: After 2 to 5 months on MEPED treatment, CT scans showed partial remissions in all three patients. Two patients had achieved PET Deauville score 2 and 3, while the third remained positive at Deauville score 5. One patient achieving PR became eligible for alloHSCT, while the other two patients continued treatment with MEPED. All patients eventually achieved continuous complete remission (cCR), one after consecutive alloHSCT, one after discontinuing MEPED consolidation for > 1 year and one on on-going MEPED consolidation, respectively. Only one patient experienced Grade 3 toxicity (bacterial pneumonia) requiring temporary discontinuation of MEPED for 10 days. Conclusion: MEPED is well tolerated with low toxicity and highly efficacious in relapsed/refractory cHL, including severely comorbid patients. Due to its immunomodulatory components, MEPED might also have a synergistic potential when combined with ICPi but requires further evaluation within a clinical trial.